2016
DOI: 10.1007/s00221-016-4673-x
|View full text |Cite
|
Sign up to set email alerts
|

Defining filled and empty space: reassessing the filled space illusion for active touch and vision

Abstract: In the filled space illusion, an extent filled with gratings is estimated as longer than an equivalent extent that is apparently empty. However, researchers do not seem to have carefully considered the terms filled and empty when describing this illusion. Specifically, for active touch, smooth, solid surfaces have typically been used to represent empty space. Thus, it is not known whether comparing gratings to truly empty space (air) during active exploration by touch elicits the same illusionary effect. In Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Finally, in Experiment 2 we also tested whether perceived grasping capacity would influence perceived object size if objects were presented haptically as well as visually. Both vision and active touch (haptics) process spatial information (Collier & Lawson, 2016; Lawson, 2009; Lawson, Ajvani, & Cecchetto, in press). Active exploration of the environment is critical to learning about the action capacity of the hands, and Gori and colleagues have shown that haptic information calibrates visual estimates of object size in young children (Gori, Del Viva, Sandini, & Burr, 2008; Gori, Sciutti, Burr, & Sandini, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, in Experiment 2 we also tested whether perceived grasping capacity would influence perceived object size if objects were presented haptically as well as visually. Both vision and active touch (haptics) process spatial information (Collier & Lawson, 2016; Lawson, 2009; Lawson, Ajvani, & Cecchetto, in press). Active exploration of the environment is critical to learning about the action capacity of the hands, and Gori and colleagues have shown that haptic information calibrates visual estimates of object size in young children (Gori, Del Viva, Sandini, & Burr, 2008; Gori, Sciutti, Burr, & Sandini, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Tactile perception begins with some interaction between the skin and external stimuli to which mechanoreceptors in the skin respond. Although often caused by contact with a solid surface, humans are also sensitive to a cool breeze on a summer day, kinesthetic cues arising from movement through air (Collier and Lawson 2016) or a drop of hot water erroneously encountering the skin while making a cup of coffee. Even bending of the hairs on hairy skin can give rise to a perceptual experience (Gibson 1962).…”
Section: Introductionmentioning
confidence: 99%
“…The visual illusion that is named after Oppel (1860–1861) and Kundt (1863) consists in the overestimation of extents that are filled with items relative to otherwise equal, empty extents. The illusion can also be observed in the haptic-tactile sense modality (Collier & Lawson, 2016) and in 3D space (Deregowski & McGeorge, 2006) but will here be considered for vision and the Euclidean plane only. For these conditions, the prototype illustration of the illusion, a forerunner of which was introduced by Wundt (1898), is a horizontal, continuous line, the endpoints of which as well as one half of which are marked with short, orthogonal, symmetrically bisected, equally spaced ticks (Mikellidou & Thompson, 2014).…”
mentioning
confidence: 99%
“…The visual illusion that is named after Oppel (1860Oppel ( -1861 and Kundt (1863) consists in the overestimation of extents that are filled with items relative to otherwise equal, empty extents. The illusion can also be observed in the haptic-tactile sense modality (Collier & Lawson, 2016) and in 3D space (Deregowski & McGeorge, 2006) but will here be considered horizontal, the Oppel-Kundt and the horizontal-vertical effects work against each other, so that the bias should decrease.…”
mentioning
confidence: 99%